2015
DOI: 10.1038/srep12292
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic stress activates the expression of members of the miR-15/107 family and induces downregulation of anti-apoptotic genes in rat liver

Abstract: microRNAs are an abundant class of small non-coding RNAs that negatively regulate gene expression. Importantly, microRNA activity has been linked to the control of cellular stress response. In the present study, we investigated whether the expression of hepatic microRNAs is affected by changes in ambient osmolarity. It is shown that hyperosmotic exposure of perfused rat liver induces a rapid upregulation of miR-15a, miR-15b and miR-16, which are members of the miR-15/107 microRNAs superfamily. It was also iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Bacteria can enact changes in miR expression in cells (Jin et al, 2014, Naeem et al, 2012). Additionally, it has been shown that reactive oxygen species (ROS), for example triggered by bacteria in the ulcers, can induce the miR-15 family (Dhall et al, 2014, Dunnill et al, 2015, Santosa et al, 2015). Therefore, S. aureus -mediated induction of miR-15b-5p found in DFUs and infected acute wounds suggests this mechanism of action to inhibit healing.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria can enact changes in miR expression in cells (Jin et al, 2014, Naeem et al, 2012). Additionally, it has been shown that reactive oxygen species (ROS), for example triggered by bacteria in the ulcers, can induce the miR-15 family (Dhall et al, 2014, Dunnill et al, 2015, Santosa et al, 2015). Therefore, S. aureus -mediated induction of miR-15b-5p found in DFUs and infected acute wounds suggests this mechanism of action to inhibit healing.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic expression of highly conserved miR‐15 members is associated with cellular pro‐apoptotic activity (Cimmino et al, ). It was also shown in rodents that when miR‐15 family are inhibited, they were protected against cardiomyocyte apoptosis after myocardial infarction (Hullinger et al, ), and miR‐15a was also linked to the control of responses of cells to stress (Santosa, Castoldi, Paluschinski, Sommerfeld, & Haussinger, ). The molecular mechanisms of how miR‐15a modulates sperm function in the bovine are yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of miR-15a, miR-15b and miR-16 were increased in rat livers which perfused with hyperosmotic solution. Upregulated miR-15a, miR-15b and miR-16 contribute to cell death through the inhibition of anti-apoptotic genes, such as Bcl2, CD-1, protein carboxyl- O -methyltransferase (Pcmt1) [ 33 ]. miR-15 family regulates TGF-β signaling pathway by targeting TGFβr1, Smad3, Smad7, p38 and endoglin directly or indirectly in cardiac fibrosis [ 30 ].…”
Section: The Mir-15 Family Members Have a Positive Impact On Tgf-β Simentioning
confidence: 99%